1997
DOI: 10.1017/s0952523800011780
|View full text |Cite
|
Sign up to set email alerts
|

Spiking and nonspiking models of starburst amacrine cells in the rabbit retina

Abstract: The integrative properties of starburst amacrine cells in the rabbit retina were studied with compartmental models and computer-simulation techniques. The anatomical basis for these simulations was provided by computer reconstructions of intracellularly stained starburst amacrine cells and published data on dendritic diameter and biophysical properties. Passive and active membrane properties were included to simulate spiking and nonspiking behavior. Simulated synaptic inputs into one or more compartments consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…However, subsequent modeling studies indicated that the electrical isolation of dendrites in starburst cells depends on assumptions of either relatively low specific membrane resistance or minimal synaptic coactivation of individual dendrites (Poznanski, 1992;Velte and Miller, 1997). Our observation (illustrated in Figure 1) that it was difficult to depolarize starburst cell somata beyond Ϫ20 mV suggests that Kv3 currents generate a voltage-dependent shunt located proximally, which prevents effective depolarization of the starburst cell soma.…”
Section: Role Of Kv3 Channels In Starburst Amacrine Cellsmentioning
confidence: 81%
See 1 more Smart Citation
“…However, subsequent modeling studies indicated that the electrical isolation of dendrites in starburst cells depends on assumptions of either relatively low specific membrane resistance or minimal synaptic coactivation of individual dendrites (Poznanski, 1992;Velte and Miller, 1997). Our observation (illustrated in Figure 1) that it was difficult to depolarize starburst cell somata beyond Ϫ20 mV suggests that Kv3 currents generate a voltage-dependent shunt located proximally, which prevents effective depolarization of the starburst cell soma.…”
Section: Role Of Kv3 Channels In Starburst Amacrine Cellsmentioning
confidence: 81%
“…These data suggest that the direction-selective properties of starburst cells arise from intrinsic mechanisms likely to include both passive and active membrane properties (Poznanski, 1992;Velte and Miller, 1997;Euler et al, 2002). However, the specific ion channels present in starburst cells are essentially unknown.…”
Section: Introductionmentioning
confidence: 97%
“…If SACs show regenerative membrane properties then it would be difficult to justify the existence of electrotonically isolated dendritic compartments within SACs (cf. [116]). The earlier models of SACs incorporating active membrane properties were based on inadequate assumptions (see for example, [107,116]).…”
Section: The Road To the Presynaptic Model Underlying Direction Selecmentioning
confidence: 99%
“…The earlier models of SACs incorporating active membrane properties were based on inadequate assumptions (see for example, [107,116]). For instance, Velte and Miller [116] developed a compartmental model of a single SAC with active ionic currents found in ganglion cells from intact amphibian retina. Such modeling should be treated with skepticism, as there is a serious hazard in generalizing across species.…”
Section: The Road To the Presynaptic Model Underlying Direction Selecmentioning
confidence: 99%
“…4) [31]. In combination with the morphology and the differential distribution of ion channels along the SAC dendrite, this leads to electrical isolation of the sectors from each other [57,82]. As a result, the individual dendritic sectors can be considered as largely independent processing units [10,28,57,77].…”
Section: Introductionmentioning
confidence: 99%